Internationalisation Of Malaysian Architectural Firms - Azmi, Haniza Azmaya C. M. Nor (2010)
Several Malaysian architectural firms have spread their architectural influence in the international markets, even making their mark on several prestigious projects. This study aimed to investigate the differences between internationalised and non-internationalised firms, the motives that drove internationalised firms to go overseas, the firm-specific and home country-specific factor they possessed, the locational factors they considered, the strategies they adopted to internationalise and the implication of firm size and age among internationalised firms.